Formulation and evaluation of acetaminophen suspension using fenugreek seeds as a natural suspending agent - Khan, Ahmed Tareque (BRAC Univeristy, 2018)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2017.